Phagocytosis - Uribe-Querol, Eileen (Henry Stewart Talks, 2023)
Phagocytosis, Nonprofessional phagocytes and professional phagocytes, Phagocytosis steps, Recognition of the target particle, Activation of the internalization process, Phagosome formation, Phagosome maturation